A speculative synthesis of ubuntu pedagogy and constructivism for inclusive South African higher education - Gunkel, Carmen Merle; de Villiers, Courtney Jade (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
South Africa seeks to address transformation in education by wrestling with systemic issues such as unequal resource distribution, accessibility, and issues of social justice resulting from the country’s colonial and apartheid histories. These legacies, in increasingly globalised contexts, have and continue to marginalise African Indigenous Knowledge Systems (AIKS) and subjugate African academic perspectives. As such, South African higher education arguably remains rooted in overtly Eurocentric pedagogical practices and is predominantly underscored by constructivism in the 21st century. This article interrogates the responsiveness and relevance of these hegemonic approaches in the way they address the diverse needs of South African students and describes the potential of an AIKS framework as an approach to indigenous preservation. Ubuntu pedagogy, grounded in the indigenous African philosophy of Ubuntu, is not positioned in dialectical opposition to constructivism, nor as a sole alternative to existing Western approaches. Instead, the article critically compares and juxtaposes Ubuntu pedagogy with the constructivist teaching approach as it is currently operationalised in South African higher education. Outlining the synergies and divergences between these two perspectives allows for new lines of inquiry to be drawn, while also highlighting and contributing to the existing but limited body of knowledge that classifies Ubuntu as a possible contextually responsive approach to teaching and learning in the South African higher education landscape.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 6, Volume 9, 2025
Keywords: Decolonisation; Glocalisation; African Indigenous Knowledge systems; Ubuntu pedagogy; Constructivism; Globalization; Education; Glocalization -- South Africa; Ethnoscience -- South Africa; Education higher, South Africa; Inclusive education -- South Africa; Ubuntu (Philosophy); Educational change